EVALUATING THE IMPLEMENTATION OF PEDIATRIC DHF CLINICAL PATHWAY IN TYPE D HOSPITAL IN YOGYAKARTA - Cornel Anggara; Merita Arini; Ikhlas M. Jennie (Universitas Negeri Gorontalo, 2021)
AbstractBackground: Dengue haemorrhagic fever (DHF) is an endemic disease that has a high incidence and mortality rate in Indonesia. Implementating clinical pathways (CP) in hospitals can be used as the basis for treating patients with DHF so as to improve service quality and minimize complications. Objective: This study aims to evaluate the implementation of CP DHF in the pediatric unit at Type D Private Hospital in Yogyakarta. Methods: This is a mix method research with case study design. Qualitative data was collected through in-depth interviews and observations of pediatricians n=2), nurses (n=3), directors of medical services (n=1) and medical committees (n=1). Quantitative data was collected through document review and interviews with the Integrated Clinical Pathway Appraisal Tools (ICPAT). Results: Documents is true a CP. The role of the organization has been running well. The process of documenting, developing and implementing CP DHF is not optimal. The maintenance process is bad. Compliance completes of CP DHF is 9%. The majority of lenght of stay are above 3.86 days with treatment costs above the BPJS package. The incidence of complications is low. The obstacles found during the implementation of CP DHF were that the patient did not have access to CP, low adherence to CP and human resource management factors. Conclusion: The development and implementation of CP DHF needs to be improved both in terms of content and quality. Strong policies are needed, good organizational support and the active role of clinicians are the keys to the successful implementation of CP.Keywords: Clinical Pathway, Dengue Haemorragic Fever, Integrated Services